Assessment of the impact of thermal energy storage operation strategy on parabolic trough solar power plant performance. (January 2023) - Bouziane, Hamza; Benhamou, Brahim
Abstract: This numerical study aims at assessing the impact of the thermal energy storage (TES) operation strategy on the performance of a parabolic trough concentrated solar power plant (PT-CSP). This strategy consists of managing the TES charging process in order to minimize the plant's parasitic consumption. The study was conducted using a TRNSYS based dynamic simulation model of a 55 MWe PT-CSP plant similar to the ANDASOL plant located in the South of Spain. The simulation results were validated in comparison with the available experimental data in the literature. The results showed that the suggested operating strategy is efficient as the heat transfer fluid and the TES molten salt pumps' total parasitic consumption is reduced by 21% during a typical clear day of July. Consequently, the plant's net energy production was improved by 0.8%. The resulting improvement in the overall efficiency of the plant was found to be 2.4%.